Invisible ground water machine sebagai forest fire risk mitigation di Gunung Arjuno - Tasya Khairunisa; Eva Indra Sofiana; Runing Fikriyah Asyarifah; Robby Hilmi Rachmadian; Alfyananda Kurnia Putra (Universitas Negeri Malang, 2021)
Forest fires are a phenomenon of spreading fire that causes disruption of ecosystems in forest areas. The phenomenon of forest fires often occurs in Indonesia today. This can be indicated through BNPB data which shows that in 2019 there were 1,592,010 hectares of forest and burned land, most of which occurred in mountainous areas and were included in the category of protected forest and conservation forest. One of the mountains hit by forest fires is Mount Arjuno. Mount Arjuno is a mountain located on the border of Batu City, Malang and Pasuruan Regencies. From July to October 2019, the Mount Arjuno Forest experienced fires in the Seriti Curah area, the Sawahan Ringgit Block and the Gumandar Block, most of which were located at an altitude of 2,800 meters above sea level and had a slope of 70°, so it took a long time to extinguish the fire in the area. The purpose of the preparation of this idea is to create a technological innovation that is able to overcome forest fires on Mount Arjuno. The methodology used in the preparation of this paper is a research and development method. In this method, the authors collect data, design ideas, validate designs, and compile the paper. The types of data used are quantitative and qualitative. Based on these problems, the authors propose appropriate technological innovations in the form of: “Invisible Ground Water Machine” which consists of a groundwater water pumping component that can be used to extinguish fires quickly and remote sensing that can detect forest fires in real time, so as to minimize the risk posed by forest fires in mountainous areas. Kebakaran hutan ialah fenomena menjalarnya api yang menyebabkan terganggunya ekosistem di kawasan hutan. Fenomena kebakaran hutan kerap terjadi di Indonesia saat ini. Hal tersebut dapat diindikasikan melalui data BNPB yang menunjukkan bahwa pada tahun 2019 terdapat 1.592.010 hektar hutan dan lahan terbakar yang sebagian besar terjadi di daerah pegunungan dan masuk dalam kategori hutan lindung maupun hutan konservasi. Salah satu pegunungan yang dilanda kebakaran hutan yaitu Gunung Arjuno. Gunung Arjuno merupakan gunung yang terletak di perbatasan Kota Batu, Kabupaten Malang dan Pasuruan. Pada bulan Juli hingga Oktober 2019, Hutan Gunung Arjuno mengalami kebakaran di kawasan Curah Seriti, Blok Sawahan Ringgit dan Blok Gumandar yang sebagian besar berada di ketinggian 2.800 mdpl dan memiliki kemiringan lereng sebesar 70°, sehingga membutuhkan waktu lama untuk memadamkan api di kawasan tersebut. Tujuan dari penyusunan gagasan ini adalah untuk menciptakan suatu inovasi teknologi yang mampu mengatasi kebakaran hutan di Gunung Arjuno. Metodologi yang digunakan dalam penyusunan makalah ini berupa metode research and development. Pada metode ini, penulis melakukan pengumpulan data, desain gagasan, validasi desain, dan menyusun pada makalah. Jenis data yang digunakan bersifat kuantitatif dan kualitatif. Berdasarkan permasalahan tersebut, penulis mengusulkan inovasi teknologi tepat guna berupa “Invisible Ground Water Machine” yang terdiri dari komponen water pumping air tanah yang dapat digunakan untuk memadamkan api dengan cepat dan penginderaan jauh yang dapat mendeteksi kebakaran hutan secara real time, sehingga dapat meminimalisir risiko yang ditimbulkan dari kebakaran hutan di daerah pegunungan.